Comparison of perinatal outcomes in facilities before and after Global Network's Helping Babies Breathe Implementation Study in Nagpur, India - Archana Patel; Akash Bang; Kunal Kurhe; Savita Bhargav; Amber Prakash; Spoorthy Arramraj; Patricia L. Hibberd (BMC, 2019)
Abstract Background The Helping Babies Breathe (HBB) educational program focuses on training of first-level birth attendants in neonatal resuscitation skills for the first minute of life (The Golden Minute). Pre-post studies of HBB implementation in sub-Saharan Africa and Asia have shown reductions in facility-based very early neonatal mortality and stillbirth rates. However, the Global Network pre-post HBB Implementation Study (GN-HBB-IS) found no difference in day 7 perinatal mortality rates (PMR-D7) among births to women participating in the Global Network's Maternal and Newborn Health Registry. To address potential differences in perinatal outcomes in births occurring in facilities that implemented HBB vs. all births occurring in the communities served by facilities that implemented HBB, we compared day-1 perinatal mortality rates (PMR-D1) among births occurring pre and post HBB implementation in facilities in Nagpur, India, one of the 3 sites participating in the GN-HBB-IS. Methods We hypothesized that there would be a 20% decrease in the Nagpur facility based PMR-D1 in the 12 months post GN HBB implementation from the pre-period. We explored pre-post differences in stillbirth rates (SBR) and day-1 neonatal mortality rates (NMR-D1). Results Of the 15 facilities trained for the GN-HBB-IS, 13 participated in the Nagpur HBB Facility Study (Nagpur-HBB-FS). There were 38,078 facility births in the 12 months before the GN-HBB-IS and 40,870 facility births in the 12 months after the GN-HBB-IS. There was 11% overlap between the registry births analyzed in the GN-HBB-IS and the facility births analyzed in the Nagpur-HBB-FS. In the Nagpur-HBB-FS, there was a pre-post reduction of 16% in PMR-D1 (p = 0.0001), a 14% reduction in SBR (p = 0.002) and a 20% reduction NMR-D1 (p = 0.006). Conclusions In the Nagpur-HBB-FS, PMR-D1, stillbirths and NMR-D1 were significantly lower after HBB implementation. These benefits did not translate to improvements in PMR-D7 in communities served by these facilities, possibly because facilities in which HBB was implemented covered an insufficient proportion of community births or because additional interventions are needed after day 1 of life. Further studies are needed to determine how to translate facility-based improvements in PMR-D1 to improved neonatal survival in the community. Trial registration The Global Network HBB Implementation Study (GN-HBB-IS) was registered at ClinicalTrials.gov: NCT01681017.